2013
DOI: 10.1016/j.amjcard.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function and Long-Term Outcomes in Patients With Normal Exercise Echocardiographic Findings

Abstract: The objective of this study was to determine whether diastolic dysfunction (DD) is associated with outcomes in the absence of myocardial ischemia. We studied 2,835 patients undergoing exercise echocardiography (ExEcho) from January 2006 through December 2006 who had normal systolic function (ejection fraction ≥50%) and absence of exercise-induced wall motion abnormalities. Diastolic function was graded as normal, mild DD, or moderate/severe DD. Medical record review and patient contact was undertaken to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“… 13 , 34 Left ventricular diastolic dysfunction was correlated to poor CV prognosis. 35 37 In our study, the multivariable analysis consistently revealed that increased E/E′ and old age were independently associated with increased EAT thickness. Old age is a well-recognized risk factor of adverse CV events.…”
Section: Discussionsupporting
confidence: 67%
“… 13 , 34 Left ventricular diastolic dysfunction was correlated to poor CV prognosis. 35 37 In our study, the multivariable analysis consistently revealed that increased E/E′ and old age were independently associated with increased EAT thickness. Old age is a well-recognized risk factor of adverse CV events.…”
Section: Discussionsupporting
confidence: 67%
“…192 In patients with normal systolic function and absence of exerciseinduced wall motion abnormalities, the ratio of early mitral inflow diastolic velocity to early mitral annulus diastolic velocity (E/eʹ) measured at the time of ESE has been shown to be independently associated with clinical outcomes including mortality, cardiovascular events, and heart failure or hospitalization during long-term followup. 193 Among patients undergoing DSE, those who developed ischemia had lower diastolic annulus velocities at baseline (5.7 6 1.9 vs 6.4 6 1.9 cm/sec, P = .02) and at peak stress (5.2 6 1.6 vs 7.4 6 2.4 cm/s, P < .0001). The increase in E/eʹ was greater in patients who presented with dyspnea, and E/eʹ at peak stress was higher in those with ischemia and persisted into recovery.…”
Section: Stress Echocardiography In Patients With Dyspneamentioning
confidence: 86%
“…LV diastolic dysfunction is reportedly an independent predictor of mortality in patients with acute MI [ 23 ] and in patients with HF [ 5 , 24 ]. LV diastolic dysfunction was also recently demonstrated to be an independent predictor of mortality, even in patients with preserved LVEF [ 25 , 26 ]. However, in all of those studies, LV diastolic function was noninvasively evaluated using Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 99%